Diagnosis and Management of Oral Lesions and Conditions A Resource Handbook for the Clinician - Migliorati, Cesar A.; Panagakos, Fotinos S. (IntechOpen, 2014)
This handbook has the goal of providing a short and objective approach to the diagnosis and management of common oral lesions and conditions likely to be encountered in the daily practice of dentistry by the general practitioner. Each of the lesions/conditions will be grouped based on their nature, inflammatory or infectious, benign or malignant, variants of normal, bony lesions, etc. The individual lesion/condition will be described based on common clinical signs and symptoms, differential diagnosis, best approach for diagnostic confirmation, and brief management strategy. One of the chapters is dedicated to oral hygiene and oral health maintenance recommendations. Diagnosis and Management of Oral Lesions and Conditions: A Resource Handbook for the Clinician has been produced and distributed through an educational grant from the Colgate-Palmolive Company.